Gentamicin-attenuated Leishmania infantum vaccine: protection of dogs against canine visceral leishmaniosis in endemic area of southeast of Iran. - Hamid Daneshvar; Mohammad Javad Namazi; Hossein Kamiabi; Richard Burchmore; Sarah Cleaveland; Stephen Phillips (Public Library of Science (PLoS), 2014)
An attenuated line of Leishmania infantum (L. infantum H-line) has been established by culturing promastigotes in vitro under gentamicin pressure. A vaccine trial was conducted using 103 naive dogs from a leishmaniosis non-endemic area (55 vaccinated and 48 unvaccinated) brought into an endemic area of southeast Iran. No local and/or general indications of disease were observed in the vaccinated dogs immediately after vaccination. The efficacy of the vaccine was evaluated after 24 months (4 sandfly transmission seasons) by serological, parasitological analyses and clinical examination. In western blot analysis of antibodies to L. infantum antigens, sera from 10 out of 31 (32.2%) unvaccinated dogs, but none of the sera from vaccinated dogs which were seropositive at >100, recognized the 21 kDa antigen of L. infantum wild-type (WT). Nine out of 31 (29%) unvaccinated dogs, but none of vaccinated dogs, were positive for the presence of Leishmania DNA. One out of 46 (2.2%) vaccinated dogs and 9 out of 31 (29%) unvaccinated dogs developed clinical signs of disease. These results suggest that gentamicin-attenuated L. infantum induced a significant and strong protective effect against canine visceral leishmaniosis in the endemic area.